Tracking eolian dust with helium and thorium: Impacts of grain size and provenance. (15th February 2016) - McGee, David; Winckler, Gisela; Borunda, Alejandra; Serno, Sascha; Anderson, Robert F.; Recasens, Cristina; Bory, Aloys; Gaiero, Diego; Jaccard, Samuel L.; Kaplan, Michael; McManus, Jerry F.; Revel, Marie; et al.
Abstract: Reconstructions of the deposition rate of windblown mineral dust in ocean sediments offer an important means of tracking past climate changes and of assessing the radiative and biogeochemical impacts of dust in past climates. Dust flux estimates in ocean sediments have commonly been based on the operationally defined lithogenic fraction of sediment samples. More recently, dust fluxes have been estimated from measurements of helium and thorium, as rare isotopes of these elements (He-3 and Th-230) allow estimates of sediment flux, and the dominant isotopes (He-4 and Th-232) are uniquely associated with the lithogenic fraction of marine sediments. In order to improve the fidelity of dust flux reconstructions based on He and Th, we present a survey of He and Th concentrations in sediments from dust source areas in East Asia, Australia and South America. Our data show systematic relationships between He and Th concentrations and grain size, with He concentrations decreasing and Th concentrations increasing with decreasing grain size. We find consistent He and Th concentrations in the fine fraction (<5 μm) of samples from East Asia, Australia and Central South America (Puna-Central West Argentina), with Th concentrations averaging 14 μg/g and He concentrations averaging 2 μcc STP/g. We recommend use of these values for estimating dust fluxes in sediments where dust is dominantly fine-grained, and suggest that previous studies may have systematically overestimated Th-based dust fluxes by 30%. Source areas in Patagonia appear to have lower He and Th contents than other regions, as fine fraction concentrations average 0.8 μcc STP/g and 9 μg/g for 4 He and 232 Th, respectively. The impact of grain size on lithogenic He and Th concentrations should be taken into account in sediments proximal to dust sources where dust grain size may vary considerably. Our data also have important implications for the hosts of He in long-traveled dust and for the 3 He/ 4 He ratio used for terrigenous He in studies of extraterrestrial He in sediments and ice. We also investigate the use of He/Th ratios as a provenance tracer. Our results suggest differences in fine fraction He/Th ratios between East Asia, Australia, central South America and Patagonia, with ratios showing a positive relationship with the geological age of source rocks. He/Th ratios may thus provide useful provenance information, for example allowing separation of Patagonian sources from Puna-Central West Argentina or Australian dust sources. He/Th ratios in open-ocean marine sediments are similar to ratios in the fine fraction of upwind dust source areas. He/Th ratios in mid-latitude South Atlantic sediments suggest that dust in this region primarily derives from the Puna-Central West Argentina region (23–32°S) rather than Patagonia (>38°S). In the equatorial Pacific, He/Th ratios are much lower than in extratropical Pacific sediments or potential source areas measured as a part of this study (East Asia, South America, Australia) for reasons that are at present unclear, complicating their use as provenance tracers in this region.